Efforts of PAI Teachers in Increasing Student Learning Interest with Project Based Learning Strategies in the 2013 Curriculum at SD 060851 - Neliwati Neliwati; Zaidan Zega; Jekson Parulian Harahap; Siti Syaidariyah Hasibuan (Edumaspul: Jurnal Pendidikan, 2022)
Teachers can use project-based learning to accelerate the learning process and improve students' critical thinking skills. Project Based Learning (PBL) can be used in two ways: either by individuals or groups working towards a common goal (such as making a product). In contrast, the approach taken in this research is descriptive qualitative, in which the research questions posed and the answers they generate provide a picture of the situation. All students in grade four are the focus of research. The research results show that 80% of project-based learning strategies are effective and can be used in learning models.